Brilliant retirement your practical guide to a happy, healthy, financially sound retirement - Peeling, Nic (Pearson, 2010)
Nic Peeling recently retired from his managerial position with Qinetic. He is a research scientist by background and is the author of the bestselling book Brilliant Manager. This book is the result of Nic's mission to bring together personal experiences and the latest research into one entertaining and easy to read book, packed with the kind of information, help and advice he just couldn't find when he was retiring.